Maternal input and infants' response to infant‐directed speech. (20th April 2020) - Outters, Vivien; Schreiner, Melanie S.; Behne, Tanya; Mani, Nivedita
Abstract: Caregivers typically use an exaggerated speech register known as infant‐directed speech (IDS) in communication with infants. Infants prefer IDS over adult‐directed speech (ADS) and IDS is functionally relevant in infant‐directed communication. We examined interactions among maternal IDS quality, infants' preference for IDS over ADS, and the functional relevance of IDS at 6 and 13 months. While 6‐month‐olds showed a preference for IDS over ADS, 13‐month‐olds did not. Differences in gaze following behavior triggered by speech register (IDS vs. ADS) were found in both age groups. The degree of infants' preference for IDS (relative to ADS) was linked to the quality of maternal IDS infants were exposed to. No such relationship was found between gaze following behavior and maternal IDS quality and infants' IDS preference. The results speak to a dynamic interaction between infants' preference for different kinds of social signals and the social cues available to them.